Narrativas sobre a cultura na formação profissional dos assistentes sociais: perspectivas docentes - Hurtado, Liliana Espinosa (2016)
The professional formation of social workers in Brazil has historically been the focus of discussion within the category, searching to follow societal changes that challenge the Social Service. The research presented here aimed to critically analyze the appropriation of culture category in the social workers’ undergraduate vocational training level, from the 1990’s on, in São Paulo State. Our proposal was linked to the understanding of culture in the social workers’ professional formation from the 90’s curriculum reform on and, to achieve that, we analyzed this category’s inclusion through teachers’ narratives in the materiality of the subjects taught by them in four Social Work full curricular programs. We developed a qualitative research that, in one instance, used semi-structured interviews which were analyzed based on the principles of grounded theory. In another instance, an analytical description of the chosen subjects teaching programs in the four social service programs that were part of the survey was conducted. We found that there is a historical materialist perspective primacy in the treatment of this category within the disciplines, although great historical phenomena are worked, the emphasis is, in most disciplines, approach the culture in a more private and regional sense, associated with the present diversity in the territories and phenomena related to problems that generate cultural differences. This view of culture category is addressed by teachers transiting between the material and symbolic aspect of it. We concluded that culture is worked in the disciplines depending on the teachers’ perspective, and this is influenced by training and disciplinary field to which it belongs, in addition to their personal experiences related to their professional practice as a militant, teacher, researcher or intervening